Changes in the Association Between Diagnostic Testing Method, Polymerase Chain Reaction Ribotype, and Clinical Outcomes From Clostridioides difficile Infection: One Institution's Experience. (31st October 2020) - Menon, Anitha; Perry, D Alex; Motyka, Jonathan; Weiner, Shayna; Standke, Alexandra; Penkevich, Aline; Keidan, Micah; Young, Vincent B; Rao, Krishna
Abstract: Background: In Clostridioides difficile infection (CDI), the relationship between clinical, microbial, and temporal/epidemiological trends, disease severity and adverse outcomes is incompletely understood. In a follow-up to our study from 2010–2013, we evaluate stool toxin levels and C. difficile polymerase chain reaction (PCR) ribotypes. We hypothesized that elevated stool toxins and infection with ribotype 027 associate with adverse outcomes. Methods: In 565 subjects at the University of Michigan with CDI diagnosed by positive testing for toxins A/B by enzyme immunoassay (EIA) or PCR for the tcdB gene, we quantified stool toxin levels via a modified cell cytotoxicity assay (CCA), isolated C. difficile by anaerobic culture, and performed PCR ribotyping. Severe CDI was defined by Infectious Diseases Society of America (IDSA) criteria, and primary outcomes were all-cause 30-day mortality and a composite of colectomy, intensive care unit admission, and/or death attributable to CDI within 30 days. Analyses included bivariable tests and logistic regression. Results: 199 samples were diagnosed by EIA; 447 were diagnosed by PCR. Toxin positivity associated with IDSA severity but not primary outcomes. In 2016, compared with 2010–2013, ribotype 106 newly emerged, accounting for 10.6% of strains, ribotype 027 fell from 16.5% to 9.3%, and ribotype 014–027 remained stable at 18.9%. Ribotype 014–020 associated with IDSA severity and 30-day mortality ( P = .001). Conclusions: Toxin positivity by EIA and CCA associated with IDSA severity but not with subsequent adverse outcomes. The molecular epidemiology of C. difficile has shifted, which may have implications for the optimal diagnostic strategy for and clinical severity of CDI. Abstract : Clostridioides difficile toxin detection associated with case severity but not with subsequent adverse outcomes. The molecular epidemiology of C. difficile varies over time and geography, which may have implications for the optimal diagnostic strategy for Clostridioides difficile infection at specific institutions.